Comparison of visual and electronic devices for individual identification of dromedary camels under different farming conditions. Issue 8 (1st August 2016) - Caja, G.; Díaz-Medina, E.; Salama, A. A. K.; Salama, O. A. E.; El-Shafie, M. H.; El-Metwaly, H. A.; Ayadi, M.; Aljumaah, R. S.; Alshaikh, M. A.; Yahyahoui, M. H.; Seddik, M. M.; Hammadi, M.; et al.
Abstract: The camel industry uses traditional (i.e., iron brands and ear tags) and modern (i.e., microchips) identification (ID) systems without having performance results of reference. Previously iron-branded ( n = 45; 1 yr) and microchipped ( n = 59; 7 yr) camels showed problems of healing (8.6% of brands) and reading (only 42.9% of brands and 69.5% of microchips were readable), which made their use inadvisable. With the aim of proposing suitable ID systems for different farming conditions, an on-field study was performed using a total of 528 dromedaries at 4 different locations (Egypt, n = 83; Spain, n = 304; Saudi Arabia, n = 90; and Tunisia, n = 51). The ID devices tested were visual (button ear tags, 28.5 mm diameter, n = 178; double flag ear tags, 50 by 15 mm, n = 83; both made of polyurethane) and electronic (ear tags, n = 90, and rumen boluses, n = 555). Electronic ear tags were polyurethane-loop type (75 by 9 mm) with a container in which a 22-mm transponder of full-duplex technology was lodged. Electronic boluses of 7 types, varying in dimensions (50 to 76 mm length, 11 to 21 mm width, and 12.7 to 82.1 g weight) and specific gravity (SG; 1.49 to 3.86) and each of them containing a 31-mm transponder of half-duplex technology, were all administered to the dromedaries at the beginning of the study. When a low-SG bolus was lost, a high-SG bolus was readministered. Readability rates of each ID system were evaluated during 1 to 3 yr, according to device and location, and yearly values were estimated for comparison. On a yearly basis, visual ear tag readability was not fully satisfactory; it was lower for rectangular ear tags (66.3%) than for button ear tags (80.9%). Yearly readability of electronic ear tags was 93.7%. Bolus readability dramatically varied according to their SG; the SG < 2.0 boluses were fully lost after 8 mo. In contrast, the SG > 3.0 boluses were efficiently retained (99.6 to 100%) at all locations. In conclusion, according to the expected long lifespan of camels, low ID performances were observed for iron brands, injectable microchips, and ear tags (visual and electronic), making their use inadvisable as unique ID systems in camels. The high readability of dense electronic boluses recommended their use as a permanent ID device of reference in camels.